Performance of Community Health Volunteers in the Delivery of Healthcare Services During the Covid-19 Pandemic in Nakuru, Kenya: A Cross-Sectional Analysis - Gachathi, Salome Nyambura; Walekhwa, Michael; Mugambi, Joy (JOURNAL OF CLINICAL CARE AND MEDICAL ADVANCEMENT, 2024)
In many parts of the world, including Kenya, there is a critical shortage of trained healthcare workers. In response to this, the World Health Organization (WHO) has advocated for the utilization of volunteer community members to provide essential health services within their communities. While Community Health Volunteers (CHVs) in Kenya have demonstrated positive contributions to community health, there is a dearth of data on their performance during pandemics such as COVID-19. We assessed the performance of CHWs during the COVID-19 pandemic in Nakuru County. This was a cross-sectional descriptive study with mixed methods approach. Purposive sampling was utilized to select the study sites and random sampling to sample 260 CHV participants. A standardized data collection schedule was used to collect data on key community health indicators from the District Health Information System 2 (DHIS2) in each sub-county which was used to compare CHVs’ performance before and during COVID-19. A structured questionnaire was filled out by CHVs to address the study objectives. Data was subjected to an Analysis of variance (ANOVA) test to determine differences in the periods at α=0.05. The CHVs’ routine community services significantly improved during COVID-19. There were significant differences in Maternal and Neonatal Health (MNH) services groups as determined by the Analysis of variance test (F(2, 33) = 26.341, p < .001), child services groups as determined by Analysis of variance test (F(2, 33) = 15.042, p < .001), CHVs’ care of persons with known chronic conditions services groups as determined by Analysis of variance test (F(2, 33) = 39.799, p < .001) and significant difference in CHVs’ care of geriatrics services groups as determined by Analysis of variance test (F(2, 33) = 24.778, p < .001). Pre- and Post-pandemic policies should promote CHV service utilization and consider training, proper reporting of their indicators and continuous monitoring and evaluation (M&E). New service provision methodologies such as the application of technology should be integrated into the CHVs services.
Keywords: Trained health workers; Community Health Workers; Community health strengthening; Community Health Volunteers; Disease Emergencies